2021
DOI: 10.1002/ange.202109801
|View full text |Cite
|
Sign up to set email alerts
|

Selective Approaches to α‐ and β‐Arylated Vinyl Ethers

Abstract: We developed simple and efficient protocols for palladium-catalyzed regioselective a-a nd b-arylations of structurally diverse vinyl ethers.B oth catalytic methods proceed under relatively mild reactions conditions applying to abroad substrate range including more complex compounds providing arylated glucal or isochromene.L acking the common requirement of alarge reagent excess,the transformations are highly economic and limiting the waste production. Results from computational studies (DFT) provided insight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Aryl bromides bearing electron-withdrawing groups (EWGs), including acyl, formyl, methoxycarbonyl, cyano and methylsulfonyl, reacted smoothly and the corresponding α-arylated alkenes 3-13 were obtained in moderate-to-very-good yields (47-81%). As expected, chloro-and fluorobenzenes also reacted with complete chemoselectivity (14)(15)(16)(17)(18)(19). Considering polybrominated benzenes, the mono-α-arylation products 16 and 17 were selectively formed with the additional C−Br bonds remaining untouched.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Aryl bromides bearing electron-withdrawing groups (EWGs), including acyl, formyl, methoxycarbonyl, cyano and methylsulfonyl, reacted smoothly and the corresponding α-arylated alkenes 3-13 were obtained in moderate-to-very-good yields (47-81%). As expected, chloro-and fluorobenzenes also reacted with complete chemoselectivity (14)(15)(16)(17)(18)(19). Considering polybrominated benzenes, the mono-α-arylation products 16 and 17 were selectively formed with the additional C−Br bonds remaining untouched.…”
Section: Resultssupporting
confidence: 67%
“…Considering the intrinsic regioselectivity of Mizoroki-Heck couplings, it would be highly desirable to access the irregular regioisomer of the omnipresent Mizoroki-Heck reaction, ideally by simple variation of the reaction conditions, keeping the standard substrates, thereby significantly enlarging the product space. Indeed, by manipulating the transition metal catalyst, ligand and/or aryl pseudohalide substrate, good αand β-regioselectivities can be achieved for both electron-rich and aliphatic alkenes [15][16][17][18][19][20][21][22][23] . However, electronpoor alkenes, such as acrylates and styrenes, which are probably the most widely used starting alkenes in the Mizoroki-Heck coupling reaction, usually furnish the corresponding β-coupling products highly selectively and, due to the dominating electronic factors, achieving the opposite regioselective insertion to obtain the corresponding α-arylation products is highly challenging 24,25 .…”
mentioning
confidence: 99%
“…Aryl fluorosulfates and other pseudohalides such as triflates, [108–111] tosylates, [112–114] and mesylates [115–117] are widely used in transition‐metal‐catalyzed coupling reactions. However, aryl fluorosulfates have numerous advantages as electrophilic coupling partners.…”
Section: Advantages and Activity Of Fluorosulfates Compared With Othe...mentioning
confidence: 99%
“…However, there are many exceptions to these rules of as we discuss below and some have even argued that "we cannot make any predictions about the regiochemistry of arylation ... and temptations to find simple rules should be discarded." 3 There is thus a great deal of interest in gaining a better understanding of the factors that govern the regioselectivity both theoretically [4][5][6] and experimentally. 1 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, both Deeth et al 4 , Bäcktorp and Norrby, 5 and Domzalska-Pieczykolan et al 6 have explained experimentally observed regioselectivity based on DFTcomputed barrier heights of the insertion step. Deeth et al have developed a predictive model based on DFT-computed electrostatic and orbital properties of the neutral or cationic alkene-catalyst complexes which they test on eight different alkenes.…”
Section: Introductionmentioning
confidence: 99%